Afirmação do projeto ético-político do serviço social: a utilização das técnicas das manifestações artístico-culturais no debate sobre os movimentos sociais - Narcizo, Elaine Cristina [UNESP] (2014)
This workaims todiscuss theuse of the techniquesofartistic andcultural events-poetry,theater, dance, music, literature, cinema -through Social Welfaretogether withSocial Movements, in order to establisha theoretical-methodologicalappropriation of thesetechniques tocontributewith theemancipatory perspectiveof the Social Welfare. This discussion isbased on theLukacsianaesthetics andaims to strengthenSocial Movements, thus servingas a reinforcement elementagainstthe hegemonic. Therefore, we usethe appropriationof atheoretical referencethatdisclosesthe movementof reality. To that effect, we conduct a discussion regarding theaestheticfoundations ofartfrom the conceptionofLukács work:Aesthetics, whichdeals with thesystematizationof theoreticalassumptionstowards aMarxist aesthetics, based on thedialecticalmaterialistmethod. Then, we present a reflection onthe roleand scopeof social movementsin the present conjuncture, starting from an analysisthat pointshowthe effectivenessof collective subjectsinBrazilis historically hinged tothe materialization of an ethical-political projectof the profession. Finally, we treat theAestheticsExperimentationLaboratories, an instrumentwe formulatedfrom theaction researchmethodology, which we discussed together with the students participating in the fieldwork researchin atheoretical andpractical manner,howartcan serveto conductmediationsthat enableaknowledgeableanalysis aboutthe realityand its possibilities, following the premiseof consolidatingsocial movements. Thus, thiswork aims toreflect onhow social movementscan be understoodas a concretespace for the objectification of subjects who are aestheticallydriven, taking into account, in the case of the SocialWelfare, the possibilityof encouragingmore forcefullythecollective perspective, using then the universalizingcontent ofart.Therefore, this articulation-subjectaestheticallydrivenand social movements-intended to channelthe...